Complaints to the veterinary disciplinary board related to the euthanasia of animals - Berg, Charlotte; Vickers, Hannah (Frontiers in Veterinary Science, 2024)
This article presents an analysis of the formal complaints to the Swedish Veterinary Disciplinary Board (VDB) during the years 2018–2022 related to euthanasia of animals, which are highly relevant to the One Welfare approach. The aim was to examine whether the complaints were justified or not, according to the disciplinary investigations carried out, and whether animals had been exposed to unnecessary suffering during these interventions. The reasons for the complaints were investigated and categorized. The results showed that incorrect treatment or handling of the animal was the most common reason for reporting a veterinarian to the VDB, while the main underlying cause, based on the qualitative analysis, was found to be communication barriers. However, the number of complaints leading to disciplinary outcomes (admonitions or warnings) was very low. The vast majority (45 out of 47) of complaints relating to euthanasia were therefore not legally justified as per the VDB decision, as the veterinary staff were found to have acted correctly from a veterinary and animal welfare perspective. Nevertheless, even unjustified complaints can be very stressful for the veterinarian and should be minimized.